ALIRAN PERMUKAAN PADA TEKNIK KONSERVASI TANAH GULUDAN DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR - Cindy S. Sibua; Yani Kamagi; Maria Montolalu; Wiesje Kumolontang (COCOS, 2013)
ABSTRACTAt Rurukan sub-district dry farming agricultural a large part contrived on region gets to bevel. On runoff scarp will happen faster, it because rainwater which falls will be adrift at presto surface soil, so water chance for turns in at earth as laconic and make infiltration capacity become little. Therefore needs to be done by soil conservation action as makings of terrace for earth preservation. There is aim even of this research which is to know big runoff on barrackterrace and traditional barrackon about carrot plant at Rurukan sub-district. This research doing to utilize fairish little slot method 11x4 meter. Downloading is done begin over carrot until crop instilling, data then described by descriptive point out observational result that runoff on barrackterrace slot which is 0,14 m 3 / barrackslot and slot traditional as big as 0,00 m 3 /slot.Key word: Runoff, Terrace, Compost, Rurukan